The nexus between growth of Micro, Small and Medium Enterprises (MSMEs) and youth employment in Eritrea - Malamulo,Terence Crayl (Graduate School of Business (GSB), 2019)
Economic growth and development are strategic for the overall development of a country. Micro, small and medium enterprises play a surmountable role in economic growth and development. Among other contributions, they provide jobs in an economy. Several developing countries, such as Eritrea, face limited private sector growth, yet also have the need to invest in the creation of enough and decent job for youths. Hence, this study intended to identify the prominent factors that deter the growth of micro, small and medium enterprises as well as the connection between their growth and youth employment, using a case study of Eritrea. The study used econometric research method. Through stratified sampling and a questionnaire, it collected data from 76 micro, small and medium enterprises. In the analysis, it used ordinal and binary logistic regressions, chi-square and correlation tests. The study concludes that there is no sufficient evidence that the growth of micro, small and medium enterprises influences youth employment. It finds that the growth of micro, small and medium enterprises is deterred by obstructive access to raw materials, obstructive banking regulations and obstructive general business regulations and policies. The study recommends improvement of the macro-economic conditions for pro-business sector growth, establishment of a policy on development of micro, small and medium enterprises, and a gradual liberalization of the private economy. Further, it proposes an impact investing based growth model of micro, small and medium enterprises to increase certainty on employment creation contribution. It suggests that an investment in micro, small and medium enterprises for youth employment creation that does not address the identified deterrents faces a significant impact risk.